A Guide to Fed-Batch Cultivation of Pichia pastoris on Laboratory Scale - Straumann, Marcel; Raschmanová, Hana; Haag, Valentina; Zamora, Iwo; Kovar, Karin (Methods in molecular biology (Clifton, N.J.), 2026)
Fed-batch is the most commonly used cultivation mode for industrial production of recombinant proteins with Pichia pastoris. On a laboratory scale, fed-batch culture provides a way to control the specific biomass growth rates at any pre-set value, allowing the conditions of biomass growth and recombinant product formation to be systematically studied.In this chapter, we present an accessible and versatile approach for designing, performing, and evaluating a fed-batch cultivation in laboratory-scale stirred tank bioreactors.
Keywords: bioreaktory; Data evaluation; Batch Cell Culture Techniques; kultivační média; Bioreactors; Fed-batch culture; biomasa; techniky vsádkové kultivace; Culture Media; fermentace; Saccharomycetales; Bioreactor; Bioprocess design and development; Specific productivity; Specific growth rate; Komagataella phaffii; rekombinantní proteiny; Biomass; Pichia; Recombinant Proteins; Fermentation; Feed rate; Pichia pastoris